1973
DOI: 10.1128/iai.8.6.931-937.1973
|View full text |Cite
|
Sign up to set email alerts
|

Local Antibody Response to Experimental Poliovirus Infection in the Central Nervous System of Rhesus Monkeys

Abstract: By employing the techniques of immunofluorescence and radioimmunodiffusion using 32 P-labeled poliovirus as the antigen, the immunoglobulin response to poliovirus in serum, nasopharynx, spinal fluid, and in different segments of the central nervous system (CNS) was studied after intramuscular, oral, intranasal, and intrathalamic administration of inactivated (Salk), live attenuated (Sabin), or live virulent (Mahoney) type I poliovirus. Spinal fluid γG antibody was detected after immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Perhaps the immune response to the live rabies vaccine is similar to the local antibody response found in the CNS of rhesus monkeys given intrathalamic inoculations of the Mahoney and Sabin strains of poliovirus (15); no local (CNS) antibody was produced after similar injection of inactivated vaccine, and it was suggested that the CNS, when stimulated locally by a potent, replicating vaccine, elicits a local antibody response. We were unfortunately not able to test the possible saving effect of such a local antibody response in monkeys given attenuated rabies vaccines intrathecally, since animals inoculated with those vaccines died of vaccine-induced rabies.…”
Section: Discussionmentioning
confidence: 96%
“…Perhaps the immune response to the live rabies vaccine is similar to the local antibody response found in the CNS of rhesus monkeys given intrathalamic inoculations of the Mahoney and Sabin strains of poliovirus (15); no local (CNS) antibody was produced after similar injection of inactivated vaccine, and it was suggested that the CNS, when stimulated locally by a potent, replicating vaccine, elicits a local antibody response. We were unfortunately not able to test the possible saving effect of such a local antibody response in monkeys given attenuated rabies vaccines intrathecally, since animals inoculated with those vaccines died of vaccine-induced rabies.…”
Section: Discussionmentioning
confidence: 96%
“…Ogra et a1 [26] found that rhesus monkeys inoculated in the thalamus with poliovirus type 1, either wild or vaccine strain, had levels of polio type 1 neutralizing IgG within the CNS 2 months after infection, although serum neutralizing titers were minimal or undetectable. It is unclear, however, at what intervals serum determinations were made prior to sacrifice, and the authors thought that initial stimulation of the immune response outside the CNS was not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the presumptive antibody response to RV in hamster brain tissue also was in the IgG2 class similar to the systemic response. Although CNS origin of RV antibody has not been shown, CNS antibody production to poliovirus has been demonstrated by FA technique (12), and CSF lymphocytes from multiple sclerosis patients have been shown to synthesize immunoglobulin in vitro (7,15). Further characterization of IgG2 anti-RV from hamster brain will be of interest because CSF samples from some patients with chronic brain diseases contain antibodies ofrestricted electrophoretic heterogeneity (17) and restricted immunoglobulin subclass (18).…”
Section: Resultsmentioning
confidence: 99%